Male Sex Bias in Immune Biomarkers for Tuberculosis - Bothamley, Graham H. (Frontiers in Immunology, 2021)
Males have a bias toward developing sputum smear-positive pulmonary tuberculosis, whereas other forms of the disease have an equal sex ratio. Immune responses are known to be affected by estrogen and testosterone. Biomarkers may therefore be affected by these hormones, especially between 16 and 45 years of age when the differences are most marked. Using large data sets, we examined whether the male bias was significant in terms of diagnosis or predictive ability for the development of disease in those exposed to tuberculosis. Despite the large numbers, the need to specify homogeneous population groups for analysis affected the statistical power to discount a useful biomarker. In general, males showed higher interferon-gamma responses to TB antigens ESAT-6 and CFP-10, whilst females had stronger tuberculin responses in those with sputum smear- and culture-positive tuberculosis, but smaller responses in those who were screened for tuberculosis and who did not develop disease. Importantly, in contacts of sputum smear-positive pulmonary tuberculosis, more males who did not develop tuberculosis had tuberculin skin tests in the range between 10 and 14 mm, suggesting that sex-specific cut-offs might be better than general cut-off values for determining who should receive preventive treatment. Immunocytochemistry of the tuberculin responses correlated with cell numbers only in females. Total and anti-lipoarabinomannan IgM antibody levels were lower in males, whereas total and anti-BCG IgE antibody levels were higher. Evaluation of biomarkers should take account of the spectrum of tuberculosis and male sex bias for sputum smear-positive pulmonary tuberculosis. These findings improve our understanding of how immune responses contribute to the pathogenesis of infectious tuberculosis as well as suggesting clinical applications of the differences between the sexes.